1974
DOI: 10.1203/00006450-197410000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Effect upon Thymidine Kinase in the Developing Cerebellum

Abstract: ExtractForty-nine litters of eight Sprague-Dawley rat pups were divided into four pups treated with 0.6 mg hydrocortisone acetate on the day of bir.th and four littermate controls. The mean body weight, cerebellar weight, and cerebellar DNA were significantly depressed in treated pups by 3 days of age, with all three of these measurements of growth increasing. in rate around 9 days of age, but remaining well below control values throughout 15 days of age. Body weight and cerebellar DNA were maximally depressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The lower weight gain in the T4 treated animals was similar to that described in an earlier study (Weichsel 1974a). All pups suckled vigorously throughout the experimental period, and examinations of the stomachs of the sacrificed pups showed no observable differences in milk content between the treated and control animals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The lower weight gain in the T4 treated animals was similar to that described in an earlier study (Weichsel 1974a). All pups suckled vigorously throughout the experimental period, and examinations of the stomachs of the sacrificed pups showed no observable differences in milk content between the treated and control animals.…”
Section: Discussionsupporting
confidence: 87%
“…The single dosage regimen of T4 utilized in tbis study previously has been shown to alter thymidine kin ase (TK) activity, thymidylate synthetase (TS) activity, and DNA synthesis in developing rat cerebellum (Weichsel 1974a;C/ark and Weichsel 1977). Administration of T4 in other dose regimens has been shown to alter the activity of ornithine decarboxylase (ODe) in the developing cerebellum and cortex (Anderson and Schanberg 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been made in neonatally treated rats and mice (8)(9)(10)(11). However, the longterm effects of perinatal glucocorticoid treatment have received little attention.…”
supporting
confidence: 61%
“…The estrous cycles were normal, and the reproductive organs did not suffer any apparent abnormalities. Treatments with cortisol followed by estrogen or with estrogen alone (days [11][12][13][14][15] altered the estrous cycle by prolonging the period of estrus or by eliminating the cycles altogether (persistent diestrus). The ovaries of these animals lacked corpora lutea and had hypertrophied interstitial tissue.…”
Section: Histologymentioning
confidence: 99%
“…Therefore, it is not surprising that the ability of GCs to stunt brain development in the rodent was known [14] even before Buckingham et al [15] first suggested this steroid might accelerate lung development. Since then, multiple studies have established that GCs can dramatically effect rodent cerebellar development by decreasing proliferation [16,17,18]. Unfortunately, despite these advances, it was still not clear how this decrease in proliferation is occurring or why such vulnerability would exist to begin with.…”
Section: Introductionmentioning
confidence: 99%